Effect of duration of edentulism on neutral zone position in relation to alveolar crest ridge - Ajay Jain; Ugrappa Sridevi; Ugrappa Vijay Kumar (Wolters Kluwer Medknow Publications, 2015)
Aim: The purpose of the study was to establish a relation between the crest of alveolar ridge and functionally obtained neutral zone and to determine the effect of duration of edentulism on the location of neutral zone in relation to the crest of residual alveolar ridge. Materials and Methods: The study included three groups, Group I: 15 human subjects edentulous for 0 months to 2 years, Group 2: 15 human subjects edentulous for 2 years to 5 years and Group 3: 15 human subjects edentulous for more than 5 years. Neutral zone recording was performed for each human subjects and the bucco-lingual relationship of the crest of the mandibular alveolar ridge and position of neutral zone was examined. The results were analyzed by Kruskal-Wallis h-test and Chi-square independent test. Results: The results suggested that the location of neutral zone varies from individual to individual depending on their musculature and there is significant relation to the duration of edentulism. As the duration of edentulism increases, there is more lingual positioning of neutral zone at the molar region of both side of the arch. At premolar region, there is no change in position of neutral zone, it remains constant since resorption of the alveolar ridge is directly under the buttress. In anterior region, there is more labial positioning of neutral zone as duration of edentulism increases. Conclusion: This technique proved itself to be an easy and inexpensive way to determine the relationship between the crest of alveolar ridge and neutral zone. Incorporating this technique into the practice would be a great aid, which could be exploited by the clinicians for functional and psychological comfort of the patients.